KNOWLEDGE AND PRACTICE ON BREAST SELF-EXAMINATION AMONG WOMEN OF REPRODUCTIVE AGE AT MERU TECHING AND REFERRAL HOSPITAL, MERU COUNTY, KENYA.: NURSING - Mugambi, Catherine (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
ABSTRACT Theme: Science in the Service of Climate Action Title: Knowledge and practice of breast self-examination among women of reproductive age at Meru Teaching and Referral Hospital- Meru County, Kenya. Authors: Catherine Mugambi, Dr. MaryJoy Kaimuri, Dr. Josephat Kiongo ABSTRACT Background: Breast cancer is a progressive illness with a bad prognosis when discovered late. Globally, during the year 2020, more than 2.3 million women of reproductive age were diagnosed with breast cancer and over 685 000 deaths occurred due to the disease making it the world’s most prevalent cancer. To control breast cancer incidence and reduce deaths, there is need for an early detection strategy such as breast self- examination (BSE). World Health Organization (WHO) recommends that women should start practicing breast self-examination from the age of 20 years for early detection of breast cancer. In Kenya, breast cancer screening rate is under 5% and 86 percent of women have never had a breast cancer screening making early diagnosis difficult for most of Kenyan women. Problem statement: Breast cancer screening is crucial because the disease has a preclinical stage during which the disease is localized and asymptomatic, where there are greater chances of cure and survival. Objective: The aim of this study was to assess the knowledge and practice of BSE among women of reproductive age at Meru teaching and referral hospital (MeTRH). Methods: This study used a descriptive cross-sectional study design to assess BSE knowledge and practice among 423 women of reproductive age who attended the Meru Teaching and Referral Hospital. Data was analyzed using descriptive statistics and regression analysis. Results: Majority of the respondents 58.9% (n=249) were aged between 18-28 years. Majority of the respondents (57%, n=241) had poor knowledge of BSE while 43% (n=182) had moderate knowledge of BSE. The mean score for correct breast self-examination practice was 44.4% and the standard deviation was 30. Thirty percent of the respondents (n=127) had good BSE practice, while the majority 70% (n=296) had poor BSE practice. The main determinants of BSE practice were use of teaching aids in BSE education sessions (t=9.012, p<0.001), followed by level of education (t=6.833, p<0.001), then guidance in BSE performance (t=4.87, p<0.001) and lastly the religions where the participants belonged (t=2.583, p=0.01). Conclusion: Both the level of knowledge and practice of breast self-examination was poor. Both social cultural factors and institutional factors influenced BSE practice. Recommendations: Health care providers to provide regular health education and demonstrations on BSE using appropriate teaching aids. The hospital management to regularly organize outreach programs on breast cancer screening. Key words: Breast cancer, breast self-examination, early detection, knowledge, practice, women of reproductive age, Author Catherine Mugambi Cell No: 0722994754 Email: catemugambi69@gmail.com